Liraglutide – Effects on Lean Body Mass, Muscle Mass and Prevention of Muscle Loss. A Comprehensive Literature Review - Oborski, Michał; Oborski, Krzysztof; Górski, Szymon; Okupniarek, Joanna; Ochwat, Maria; Bartosik, Michalina; Jętasiewicz, Igor; Miarczyński, Jakub; Piechocki, Paweł; Barczyńska, Katarzyna (Quality in Sport, 2026)
Introduction and Purpose. Obesity is a major global health challenge, requiring effective long-term treatments. Liraglutide, a GLP-1 agonist, is effective for weight loss and reducing visceral fat. However, its impact on lean body mass (LBM) and muscle mass is crucial, as their loss can lead to sarcopenia, metabolic impairment, and weight regain. Therefore, this literature review systematically analyses liraglutide’s effects on LBM and muscle mass in obesity and/or type 2 diabetes, and presents strategies to minimise potential muscle loss during therapy. Materials and methods. A systematic review of the scientific literature was conducted. Literature available in the PubMed and Google Scholar databases was searched using keywords. Results. The findings from clinical trials are not definitive. While several studies report a statistically significant loss of lean body mass (LBM), it remains proportionally smaller than fat loss and may constitute up to 40% of total weight reduction. Conversely, other studies—including the most recent ones—indicate that liraglutide primarily reduces adipose tissue. This effect preserves LBM and can enhance muscle quality by reducing intramuscular fat. The observed absolute decrease in LBM appears strongly correlated with total weight loss, implying it is a consequence of weight reduction itself rather than a specific drug-induced catabolic effect. Preliminary data also suggest liraglutide may have a direct anabolic and protective effect on skeletal muscle via modulation of signalling pathways. To mitigate muscle loss, pharmacotherapy should be combined with non-pharmacological interventions, such as a high-protein diet (1.2–1.6 g/kg bw/day) and regular resistance training. Combination therapies including anabolic agents also represent a promising approach.